Effects of chromophore interaction in photophysics and photochemistry of cyanine dyes. (2000) - Tatikolov, A. S.; Krasnaya, Zh. A.; Shvedova, L. A.; Kuzmin, V. A.
Abstract : Spectral and fluorescent properties of ketocyanine dyes (polyenic bis-ω, ω ′ -aminoketones) and cation-anionic polymethine dyes of various structures were studied. The symmetric ketocyanines were shown to have a long-wavelength absorption band bathochromically shifted in comparison with that of the asymmetric ketocyanines with the same total length of the polyenic chain. The nonlinear ketocyanines exhibit the additional short-wavelength band in their absorption spectra, which can be more intense than the longwavelength band. The absorption spectra of ion pairs of cation-anionic dyes with overlapping cation and anion bands contain a new intense short-wavelength band inactive in fluorescence excitation. These spectral peculiarities are explained on the basis of chromophore interaction model. It has also been shown that theT 1 levels of ketocyanine chromophores do not essentially interact with each other in a ketocyanine molecule in nonpolar solvents; in polar solvents this interaction becomes appreciable due to lowering the potential barrier for conjugation.